Geophysical and geological interpretation of cretaceous rocks (Gachetá and basal Gachetá formations) in the south Casanare area, Llanos basin (2017)
Through the integration of seismic and well data, it is possible to construct a model of the subsurface, which is analyzed to identify sandstones bodies, their stratigraphic location and possible structural deformation. This integrated interpretation is used to analyze elements of the petroleum system, such as the trap and the reservoir. The area of study is located on a basement high which, together with the regional dip of the basin have favored hydrocarbon migration. Coherence/variance, root-mean square (RMS), and spectral decomposition seismic attributes helped to define the structural and stratigraphic features, as well as the distribution of sandstones. Two structural trends are identified, the first one with a predominantly N-S direction that controls the configuration of the geobodies identified. The second with a NE-SW direction that is parallel to the direction of the deformation front of the orogen. From the Paleozoic top to the Barcos-Cuervos top, two sedimentary cycles were distinguished in the time slice: a) Gachetá Basal Fm. and Gachetá Fm. b) Guadalupe Fm. and Barcos-Cuervo Fm. The Gachetá Formation presents an approximate thickness of 300 ft., equivalent to 50 ms (TWT). The formation was divided into two intervals separated by a boundary established by an analysis developed in a previous study of stratigraphic sequences made by Cepsa. This division was made aiming to perform the supervised facies classification inside each interval. The results evidence the existence of two sedimentary cycle within the area. The first (a) has an inner shelf dominance, and the second (b) is dominated by coastal plain environments. The wells corresponding to facies 1 have the greatest sandstones content. The sandstones of the Gachetá Formation are an exploratory target and it is recommended to study further these sandstones using quantitative seismic interpretation methodology